2005
DOI: 10.1186/1471-2148-5-61
|View full text |Cite
|
Sign up to set email alerts
|

Genetic covariance between indices of body condition and immunocompetence in a passerine bird

Abstract: Background: Condition-dependence is a ubiquitous feature of animal life histories and has important implications for both natural and sexual selection. Mate choice, for instance, is typically based on condition-dependent signals. Theory predicts that one reason why condition-dependent signals may be special is that they allow females to scan for genes that confer high parasite resistance. Such explanations require a genetic link between immunocompetence and body condition, but existing evidence is limited to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 57 publications
0
11
1
Order By: Relevance
“…Although compelling examples of trade-offs between immunity and other life-history functions have been documented (Ilmonen et al 2000, Casto et al 2001, Hanssen et al 2004, Ardia 2005b, Martin et al 2008, Knowles et al 2009), results are frequently mixed and context-dependent (Williams et al 1999, Lochmiller and Deerenberg 2000, Norris and Evans 2000, Bowers et al 2012). A recent analysis of a subset of nestlings involved in this study indicates that PHA responsiveness is positively correlated with body mass (Forsman et al 2010, see also Westneat et al 2004, Gleeson et al 2005 for similar examples in other study species), contrary to what might be predicted if growth and immunodevelopment are traded off against each other. Thus, our findings for body condition and immune responsiveness are consistent with the concept of individual quality or the ability to acquire resources as a mediator of life-history trade-offs (van Noordwijk and de Jong 1986, Ardia 2005a, Love et al 2008, Hamel et al 2009a,b; Wilson and Nussey 2010, French et al 2011), contributing to variation in fitness within populations.…”
Section: Discussioncontrasting
confidence: 58%
“…Although compelling examples of trade-offs between immunity and other life-history functions have been documented (Ilmonen et al 2000, Casto et al 2001, Hanssen et al 2004, Ardia 2005b, Martin et al 2008, Knowles et al 2009), results are frequently mixed and context-dependent (Williams et al 1999, Lochmiller and Deerenberg 2000, Norris and Evans 2000, Bowers et al 2012). A recent analysis of a subset of nestlings involved in this study indicates that PHA responsiveness is positively correlated with body mass (Forsman et al 2010, see also Westneat et al 2004, Gleeson et al 2005 for similar examples in other study species), contrary to what might be predicted if growth and immunodevelopment are traded off against each other. Thus, our findings for body condition and immune responsiveness are consistent with the concept of individual quality or the ability to acquire resources as a mediator of life-history trade-offs (van Noordwijk and de Jong 1986, Ardia 2005a, Love et al 2008, Hamel et al 2009a,b; Wilson and Nussey 2010, French et al 2011), contributing to variation in fitness within populations.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies showed that this measure is negatively correlated with a stressful growth situation, in terms of both nutritional and hormonal stress, in passerine birds (e.g. [ 23 - 25 ]). In house sparrows, female condition is a positive predictor of laying date, clutch size and number of fledglings ([ 26 ] and see Methods).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, most quantitative genetic techniques require breeding experiments and are consequently largely restricted to laboratory or agricultural studies ( Falconer & Mackay 1996). Animal models have now been applied to a number of populations to tackle questions as diverse as the heritability of fitness (Kruuk et al 2000), evolutionary stasis (Meril盲 et al 2001;Kruuk et al 2002), sexual selection and coloration Hadfield et al , 2007, condition dependence (Gleeson et al 2005), parental care (MacColl & Hatchwell 2003), the genetic consequences of harvesting (Coltman et al 2003) and the evolutionary response to climate change (Brommer et al 2005).…”
Section: Introductionmentioning
confidence: 99%